Sequential Screening Strategy in Early, Middle, and Late Pregnancy in Women at High Risk of Hyperglycemia - Xu, Yi; Wei, Qiang; Zhang, Li; Duan, Mei-fan; Wang, Yue-mei; Huang, Nan (Frontiers in Endocrinology, 2022)
Background: Hyperglycaemia in pregnancy (HIP) is closely associated with short- and long-term adverse fetal and maternal outcomes. However, the screening and diagnostic strategies for pregnant women with risk factors for HIP are not set. This prospective study aimed to explore a screening strategy for women at high risk for HIP. Methods: A total of 610 pregnant women were divided into experimental (n=305) and control (n=305) groups. Pregnant women underwent a 75-g OGTT in early (<20 weeks), middle (24–28 weeks), and late pregnancy (32–34 weeks) in the experimental group and only in middle pregnancy in the control group. The general conditions, HIP diagnosis, and perinatal outcomes of the two groups were compared. Results: In the experimental group, HIP was diagnosed in 29.51% (90/305), 13.44% (41/305), and 10.49% (32/305) of patient in early, middle, and late pregnancy, respectively. The total HIP diagnosis rate was significantly higher in the experimental group (53.44% vs. 35.74%, P<0.001). Multivariate logistic regression analysis revealed that previous gestational diabetes mellitus (GDM) (odds ratio, OR=9.676, P<0.001), pre-pregnancy body mass index (BMI) ≥23 kg/m2 (OR=4.273, P<0.001), and maternal age ≥35 years (OR=2.377, P=0.010) were risk factors for HIP diagnosis in early pregnancy. Previous GDM (OR=8.713, P=0.002) was a risk factor for HIP diagnosis in late pregnancy. No significant differences in perinatal clinical data were observed between the experimental and control groups. The gestational age at delivery was significantly earlier in the experimental subgroup with early-HIP than in the experimental and control subgroups with normal blood glucose (NBG). The weight gain during pregnancy was lower in the experimental early-HIP, middle-HIP, and control NBG subgroups. Conclusions: We recommend sequential screening in early and middle pregnancy for high-risk pregnant women with maternal age ≥35 years or pre-pregnancy BMI ≥23 kg/m2, and in early, middle, and late pregnancy for high-risk pregnant women with a previous history of GDM. Trial registration: This study was registered in the Chinese Clinical Trial Registry (no. ChiCTR2000041278).